2020
DOI: 10.1097/01.nep.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas for Nursing Students and Faculty: In Their Own Voices

Abstract: AIM The aim of this national study was to explore student and faculty personal experiences of ethical dilemmas in nursing education and clinical practice. BACKGROUND Nurses encounter complex ethical dilemmas in practice that can lead to moral distress when they cannot “do the right thing” because of external constraints. METHOD A mixed-methods study via online survey was conducted on senior nursing student m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Issues and strategies relating to faculty burnout should be integrated into orientation and ongoing professional education so that well-being behaviors are embodied by faculty and integrated into existing nursing education curricula such as courses and content dealing with roles of the academic nurse educator and ethical dilemmas faced by nurse educators. [55] This can include demands unique to the type of institution, faculty track, and performance expectations and strategies for achieving balance and support. Furthermore, faculty and education programs should consider integrating well-being strategies in all levels of curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Issues and strategies relating to faculty burnout should be integrated into orientation and ongoing professional education so that well-being behaviors are embodied by faculty and integrated into existing nursing education curricula such as courses and content dealing with roles of the academic nurse educator and ethical dilemmas faced by nurse educators. [55] This can include demands unique to the type of institution, faculty track, and performance expectations and strategies for achieving balance and support. Furthermore, faculty and education programs should consider integrating well-being strategies in all levels of curricula.…”
Section: Discussionmentioning
confidence: 99%
“…25 Nursing students report situations that produce moral distress for them that are different from the situations that their faculty experience. 13 In a systematic review, issues related to health care inequities, unproductive relationships with others, and specific student characteristics impact their perception of the nursing profession and health care delivery. 26 Other sources of moral distress are related to clinical practice situations where there is dissonance between idealized values and reality, patients lack decisional capacity, and unethical situations are not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, research has indicated gaps in ethical competence of nurses to recognize and effectively address ethical issues through effective communication resulting in patterns of silence, avoidance, and distress. 12,13 Studies indicate that nurses can develop skills to mitigate the negative effects of ethical challenges by confronting moral adversity in everyday practice to foster moral resilience. 12 R3(Renewal, Resilience and Retention of Maryland Nurses) is an academic practice partnership to build statewide capacity among nursing faculty and nurse residency program (NRP) educators to deliver resilience and ethical practice content, skills, and tools to prelicensure nursing students and novice nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating such a fully integrated ethical framework will require increasing the numbers of medical and nursing faculty with formal training in bioethics as well as adding to the repertoire of experiential teaching methods. 51 Health professional programs should invest in training faculty to be skillful facilitators to enhance the student experience and avoid potential negative consequences. Shifts in virtual learning environments, in particular, require special attention to create psychologically safe spaces for learners to name and explore challenges to their ethics, mental health, and well-being.…”
Section: Effective Learning and Engagement In Ethics And Well-beingmentioning
confidence: 99%